Carbon nanotube-epoxy composites: The role of acid treatment in thermal and electrical conductivity. Issue 1 (2nd January 2017) - Metz, R.; Diaz, L.; Aznar, R.; Alvarez, L.; Flaud, V.; Ananthakumar, S.; Bantignies, J.-L.
Abstract : Wet acid oxidation treatment methods have been widely reported as an effective method to purify and oxidize the surface of industrial multi-walled carbon nanotubes. This work examines the use of a concentrated HNO3 /H2 SO4 mixture in an attempt to optimize the purification procedure of industrial multi-walled carbon nanotubes with diameter distribution statistics. It is shown that acid treatments of several hours are enough to purify the nanotubes. The electrical and thermal conductivities of epoxy composites containing 0.05–0.25 wt% of an acid-treated multi-walled carbon nanotube have been studied. The electrical conductivity of the composites decreases by more than three orders, whereas the thermal conductivity of the same specimen increases very modestly as a function of the filler content.